Experimental investigation on the effect due to mould vibrations on mechanical and metallurgical properties of aluminum alloy (a-1050) - Bobba, Sujith; Mukkollu, Sambasiva Rao; Leman, Z.; Bachina, Harish Babu (IGI Global, 2021)
In the current research work performed, the consequences caused in the casting aluminum alloy specimen due to mechanical mould vibrations are examined. Mould vibration throughout the casting provides decreased rate of shrinkage, good morphology, surface finish and lesser probability of hot tear. In this research work, the effect of mould vibration during solidification of Aluminum A-1050 alloys for dissimilar values of wavelengths at a permanent pouring temperature has been investigated to understand the modification in microstructure and mechanical properties after casting. The Al A-1050 casting has been made in a metal mould with different vibrations. The frequencies are varied from 15Hz to 50 Hz during the casting process. A casting has been made with different vibration as well to compare the results of castings with vibration frequencies. The experimental outcomes exhibited substantial grain refinement and significant increase in tensile strength and hardness of the castings with mechanical mould vibration during the duration and after solidification.